A Comprehensive Systematic Review of MRI Techniques for the Early Detection of Brain Tumors: Clinical Implications and Diagnostic Accuracy - Firmansyah, Arwan; Utama, Arya (The International Journal of Medical Science and Health Research, 2024)
Background: Brain tumours are malignancies of brain tissues. Characterising such tissues and identifying related genes can help to estimate tumour spread, and further help to identify tumour grades for the treatment planning. Such characterisation comprises of the different tumour components assessment. The aim: The aim of this study to show about MRI techniques for the early detection of brain tumors. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: MRI plays a major role in the diagnosis, grading, treatment and treatment response assessment of brain tumours and other intracranial lesions. Several adjunct MR imaging techniques have been developed to quantitatively measure a number of biophysical properties of brain tissue in vivo, allowing regional changes in the tissue microstructural environment to be better characterised. These techniques include diffusion-weighted imaging (DWI), perfusion-weighted imaging (PWI) and magnetic resonance spectroscopy (MRS).